Enhancing mobile eye-tracking in extreme urban lighting conditions - Rusnak, Marta; Koszewicz, Zofia; Hackemer, Franciszek; Garaszczuk, Izabela; Duchowski, Andrew T.; Karnicki, Rafał (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
One of the methods for understanding residents’ needs and socially improving urban spaces in terms of transportation, safety, landscape protection and managing tourist traffic load is eye-tracking (ET). Researchers using mobile ET for outdoor studies face significant challenges, particularly due to sunlight affecting data quality. Existing solutions often overlook participant comfort. This article introduces a novel accessory designed for extreme lighting conditions, such as bright days, sunsets and snowy or water-filled environments. The goal is to eliminate disruptions caused by uncontrolled sunlight on participants’ eyes, and to enable studies in urban environments. A custom sun shield, designed for ETs based on spectacle frames, prioritizes both physical and psychological comfort. The lightweight shield is easy to install, minimally restricts the field of view, and does not interfere with eye-tracking components. It is cost-effective and suitable for DIY 3D printing. Control studies and field research confirmed its effectiveness, with feedback from over 100 users improving the final design. The shield enhances eye-tracking research credibility under sunny conditions, supports efficient calibration, and improves participant recruitmen t and well-being. The quality of data obtained has improved significantly, which is manifested by a comparison of date concerning the manner of pupil detection. Thanks to this solution, it will become possible to conduct research aimed at better understanding the behavior of city users, while ensuring their comfort and safety. It will also be possible to conduct research within the framework of so-called living labs. Importantly, studies show that the approach to designing subsequent mobile ETs based on IR should undergo significant modification.